Survey on Data Integrity, Recovery, and Proof of Retrievability Techniques in Cloud Storage - Narayan Kulkarni, Neha; Kumar A. Jain, Shital; ., . (International Journal of Engineering and Technology, 2018)
Recently the technologies are growing fast, so they have become the point of source and also the sink for data. Data is generated in large volume introducing the concept of structured and unstructured data evolving "Big Data" which needs large memory for storage. There are two possible solutions either increase the local storage or use the Cloud Storage. Cloud makes data available to the user anytime, anywhere, anything. Cloud allows the user to store their data virtually without investing much. However, this data is on cloud raising a concern of data security and recovery. This attack is made by the untrusted or unauthorized user remotely. The attacker may modify, delete or replace the data. Therefore, different models are proposed for a data integrity check and proof of retrievability. This paper includes the literature review related to various techniques for data integrity, data recovery and proof of retrievability.Â Â